Evaluating Petrographic and Mechanical Property Correlations in Sihapas Formation for High-Pressure Hydraulic Fracturing Using Pearson and Spearman Methods - Prayitno, Budi; Akhillah, Daffa; Novrianti; Panuh, Dedikarni; Fitiransyah, Dike (Scientific Contributions Oil and Gas, 2026)
This study aimed to evaluate the suitability of natural frac sand (SiO₂) from the Sihapas Formation as a proppant for hydraulic fracturing in unconventional oil and gas reservoirs in Riau Province, Indonesia. Quantitative–qualitative evaluation in hydraulic fracturing systems is conducted to assess the performance of quartz grains (SiO₂) in enhancing and maintaining fluid flow conductivity under the influence of stress, formation blockage, and chemical interactions. Sieve distribution analysis was performed to determine particle size distribution, crush resistance testing was conducted to evaluate mechanical strength, and X-Ray Diffraction (XRD) was used to characterize mineral composition. The correlative relationships among parameters were further analyzed using Pearson and Spearman statistical methods, with API RP 56 (frac sand) and API 19C (proppant) standards serving as benchmarks. The results showed that the 40/70 mesh fraction dominates across samples, though roundness values fall below specification thresholds while sphericity remains within acceptable ranges. Grain hardness testing at 5000 psi showed relatively high destruction rates, while mineralogical analysis confirmed a consistently high SiO₂ composition (≥98%) with secondary clay minerals. Elevated turbidity and alkaline pH values were also observed. Statistical analysis showed strong correlations among parameters, reflecting the influence of geological transport processes on grain morphology and mineral decomposition due to diagenetic processes. In general, these findings showed that natural frac sand samples do not fully meet API standards, highlighting the need for innovation and direct well testing to enhance material quality for hydraulic fracturing applications.